ANALYSIS OF THE STATE, TRENDS AND STRUCTURAL CHARACTERISTICS OF INVESTMENT PROCESSES IN THE REGIONAL ECONOMY: IDENTIFICATION OF STRENGTHS AND WEAKNESSES, THREATS AND PROSPECTS (Development Service Industry Management, 2024)
The study analyzed the state, trends and structural characteristics of investment processes in the Lviv region. The purpose of the article is to identify strengths and weaknesses, as well as opportunities and threats to the development of investment processes in the region (using the example of Lviv region). The strengths of the economy of the Lviv region from the point of view of its investment attractiveness are indicated. The shortcomings and weaknesses of the region's investment development have been identified, among which the presence of systemic defects in the region's investment climate has been singled out; small amounts of investments (per unit of resources) and limited rates of their growth; low investment activity in sectors of the real sector of the economy with high added value; small investments in intangible assets in industries that form human and innovative potential; critically small volumes of foreign investment, in particular direct; limited public, inter-municipal and cross-border investments; underdevelopment of the system of venture financing of investments in innovation; the underdevelopment of the stock market, the small role of bank lending. The possibilities of investment development of the region are shown, as well as its threats are identified, among which the need to overcome and eliminate such threats to the further development of investment processes in the region is emphasized. These are: the prolongation of the war and the aggravation of security challenges; demographic crisis, depopulation of territories, loss of human capital; tinization and withdrawal of capital from the country; high level of external migration activity of business; loss of basic components of innovative and technological potential; strengthening of structural and spatial disparities, sectoral and sectoral disintegration; socio-political uncertainty, preservation of institutional instability.
Keywords: region; regional policy; regional development; investment; investment processes; investment activity; capital investment; volume and structure of investment